Efficacy of a simple apical negative pressure kit on smear layer removal from the root canal surface. An in vitro study - Chawin Upara; Chonsiri Vechpanich; Anat Dewi; Tanida Srisuwan; Phumisak Louwakul (Wolters Kluwer Medknow Publications, 2020)
Introduction: The objective of this study was to assess the efficacy of a simple irrigation kit, employing the apical negative pressure principle, assembled from easily obtainable materials in the dental hospital setting, on smear layer removal from the apical third of the root canal surface. Materials and Methods: The root canals of forty single-rooted mandibular premolars were mechanically prepared, and the teeth were then randomly divided into three groups to be irrigated with conventional needle irrigation (CNI) system, passive ultrasonic irrigation (PUI) system, and the simple apical negative pressure (ANP) kit. Four specimens were used as a negative control. After irrigation, the teeth were split longitudinally and examined under scanning electron microscopy at 1 mm, 3 mm, and 5 mm from the working length. The remaining smear layer was analyzed to assess the efficacy of each irrigation system. Results: The least remaining smear layer was observed in the ANP group at all three distances from the working length (P < 0.001). Furthermore, significantly less remaining smear layer was observed in the PUI group 3 mm and 5 mm from the working length than the CNI group (P < 0.01), whereas there was no significant difference between the use of PUI and CNI 1 mm from the working length. Conclusions: In this in vitro study, the assembled simple ANP kit had greater efficacy at delivering irrigants to remove the smear layer from the apical third of the root canal surface than the CNI and PUI systems.